2018
DOI: 10.1155/2018/7039790
|View full text |Cite
|
Sign up to set email alerts
|

Improved Solutions for the Optimal Coordination of DOCRs Using Firefly Algorithm

Abstract: Nature-inspired optimization techniques are useful tools in electrical engineering problems to minimize or maximize an objective function. In this paper, we use the firefly algorithm to improve the optimal solution for the problem of directional overcurrent relays (DOCRs). It is a complex and highly nonlinear constrained optimization problem. In this problem, we have two types of design variables, which are variables for plug settings (PSs) and the time dial settings (TDSs) for each relay in the circuit. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In the DOCRs coordination problem, the coordination constraints and the characteristic constraints are included in the objective function using the penalty method, as shown in equation (11). If any constraint is violated, a value of penalty is added to the objective function.…”
Section: Constraint Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the DOCRs coordination problem, the coordination constraints and the characteristic constraints are included in the objective function using the penalty method, as shown in equation (11). If any constraint is violated, a value of penalty is added to the objective function.…”
Section: Constraint Handlingmentioning
confidence: 99%
“…Teaching learning-based optimization (TLBO) and modified adaptive TLBO (MATLBO) were used in [9,10]. Firefly algorithm (FA), chaotic firefly algorithm (CFA), and modified swarm firefly algorithm (MSFA) were used in [11][12][13]. Biogeography-based optimization (BBO) along with a new hybrid BBO with linear programming (BBO-LP) was used in [14].…”
Section: Introductionmentioning
confidence: 99%
“…PPA is chosen to solve the above-mentioned problem of DOCRs. PPA was earlier implemented to design engineering problems such as gearshift problem, spring design problem and welded beam problem [14][15][16][17][18][19][20][21][22][23][24]. These problems are related to design engineering and the results obtained by PPA were good as compared to other state-of-the-art.…”
Section: Suggested Algorithmmentioning
confidence: 99%
“…In this paper, we have successfully implemented PPA [14][15][16][17][18][19][20][21][22][23][24], for the solution of standard IEEE (3, 4, and 6 bus) test systems. The two types of decision variables were PS and TDS and the sum of operating times taken by all main relays which were needed to operate for clarity of fault(s) in their respective sections.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper by [27], the hybridized symbiotic organism search method is used to deal with the directional overcurrent relay problem. The authors found the optimal coordination of directional overcurrent relays by using a firefly algorithm [28]. In the paper by [29], distributed system protection coordination is investigated based on directional overcurrent protection with an inverse time characteristic.…”
Section: Introductionmentioning
confidence: 99%